OPTIMIZING THE PROCESS OF OBTAINING MELAMINE FORMALDEHYDE RESIN USING THE BOX-WILSON METHOD (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The Box-Wilson method of mathematical planning of experiments was used in order to study the influence coefficients of the factors influencing the process of melamine synthesis on the course of the reaction.